Decoupling Global Value Chains - Peter Eppinger; Gabriel J. Felbermayr; Oliver Krebs; Bohdan Kukharskyy (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Recent disruptions to global value chains (GVCs) have raised an important question: Can decoupling from GVCs increase a country's welfare by reducing its exposure to foreign supply shocks? We use a quantitative trade model to simulate GVCs decoupling, defined as increased barriers to global input trade. After decoupling, the repercussions of foreign supply shocks are reduced on average, but some countries experience magnified effects. Across various scenarios, welfare losses from decoupling far exceed any benefits from lower shock exposure. In the U.S., a repatriation of GVCs would reduce national welfare by 2.2% but barely change U.S. exposure to foreign shocks.
Keywords: F11; F12; F14; F17; F62; 330; quantitative trade model; input-output linkages; global value chains; Covid-19; supply chain contagion; shock transmission